Reusing the structure of the PORTLEX dictionary to create a contrastive dictionary of Romance languages: a proposal. - Carlos Valcárcel Riveiro (Quaderns de Filologia: Estudis Lingüístics)
This paper proposes the development of a multilingual online dictionary for the Romance languages, called DiCoRom, using an integrative, cross-lingual and pedagogical approach. The dictionary would be based on the database structure and user interface of the existing lexicographic project PORTLEX. The objectives of DiCoRom, its target users and the necessary adaptations to the database and interface are discussed. The paper shows how the structure of PORTLEX can serve as a basis for another lexicographic project, but emphasises the need to redesign the interface to take account of the pedagogical and social orientation of DiCoRom, including the organisation of data and the inclusion of accessible examples for beginners.